2015
DOI: 10.1016/j.toxrep.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes associated with ascorbic acid–cisplatin combination therapeutic efficacy and protective effect on cisplatin-induced toxicity in tumor-bearing mice

Abstract: Cisplatin is one of the well-established anticancer drugs being used against a wide spectrum of cancers. However, full therapeutic efficacy of the drug is limited due to development of various toxicities in the host. This study examines the comparative therapeutic effectiveness and toxicities of cisplatin alone and in combination of dietary ascorbic acid (AA) in ascites Dalton's lymphoma-bearing mice. The findings show that the combination treatment of mice with ascorbic acid plus cisplatin has much better the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 90 publications
(87 reference statements)
3
26
0
Order By: Relevance
“…The most sensitive biomarkers with respect to liver cellular damage and toxicity are transaminases, because they are located in the cytoplasm and released into the circulation after cellular damage [30]. Moreover, plasma levels of BUN and creatinine have been reported as markers of platinum toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The most sensitive biomarkers with respect to liver cellular damage and toxicity are transaminases, because they are located in the cytoplasm and released into the circulation after cellular damage [30]. Moreover, plasma levels of BUN and creatinine have been reported as markers of platinum toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Since cancers may alter the metabolic and endocrine equilibrium in the host (Barbosa et al, 2009), it is reasonable that the ascorbic acid-mediated protective strategies on cisplatin-induced mutagenic effects should be tested in tumor-bearing hosts which may also propose that inspective protective agents are useful in enhancing therapeutic efficacy. Our recent studies have shown that the combination treatment using ascorbic acid with cisplatin show better antitumor activity and reduced tissue toxicities in the hosts (Amenla et al, 2013;Longchar and Prasad, 2015). Thus, the present studies were undertaken to further examine the modulatory effects of combination treatment of cisplatin with ascorbic acid on cisplatin-induced mutagenic potentials in tumor-bearing mice.…”
Section: Introductionmentioning
confidence: 94%
“…The extent of lipid peroxidation (LPO) was measured in terms of malondialdehyde (MDA) concentration in different tissues of mice using the method of Buege and Aust (1978) as described in detail earlier (Longchar and Prasad, 2015).…”
Section: Lipid Peroxidation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…This activation may occur by inducing calcium efflux from endoplasmic reticulum, generating reactive oxygen species, reducing adenosine triphosphate production, and stimulating autophagy pathway [6,7] . Further relevant studies have revealed that combining vitamin C with 5-fluorouracil, sodium dascorbate, cyclophosphamide, paclitaxel, arsenic trioxide, doxorubicin, and radiation can sensitize the cancer cells to the exposed anticancer drugs and enhance the success rate of hemo/radiotherapy [8,9] . Indeed, the clinical evaluation confirmed the major positive effect of vitamin C on enhancing the quality of life in 30-95% of cancer patients during chemo/radiotherapy procedures [9] .…”
Section: Introductionmentioning
confidence: 99%